El control administrativo y su incidencia en la gestión de inventario de la hacienda agrimont del cantón Quevedo, año 2020. propuesta: plan de mejoramiento en la gestión de stock de inventarios - Montúfar Chango, Lilibeth Belén (2021)
The objective of this research work is to determine the incidence of administrative control in the management of the inventory stock in Hacienda AGRIMONT to contribute to the efficient optimization of all the inputs that are stored in warehouses, guaranteeing an effective administration and control of the products, using standardized procedures, achieving quality in the processes and the growth of the organization. Theoretical bases are used, bibliographic references of different expert authors in the area of stock management, theories with which conclusions will be obtained to strengthen the investigation. Subsequently, the methodology to be used in the development of the project is detailed, applying field research in a more detailed way that will allow to improve the management in the management of stocks in wineries. The data collection techniques to be used will be by direct observation, interviews carried out in the areas that are linked in the chain of entry and exit of materials, such as administrators, field managers, winemakers, winery assistants and information provided by the Noboa Group., methods that will allow to evaluate the current situation of the farm with validity and veracity. In analyzing the results, the policies and procedures were determined are very important because inventory control is the process that companies use to request, receive, account for and manage the various products sold to consumers. Hacienda Agrimont has a manual of policies and procedures for the review and filing of documents in the warehouse, which is not fully complied with. Based on the warehouse management's performance in managing inventory control, the ranch generally requires that management have a purchase order with authorization prior to ordering the inventory. And with reference to the total cost of goods sold in its annual income statement, the Improvement Plan was prepared for the management of the inventory stock of the warehouses, with the procedures that provide a solution to the shortcomings in the control of the activities of the ranch, in accordance with the laws in force in the country. Keywords: Administrative control, Stock, Management, Inventory, Improvement Plan.